Responsive nanomaterials in biomedicine, patent path and prospect analysis - Liu, Xinrui; Yuan, Hongmei (Frontiers in Bioengineering and Biotechnology, 2025)
In recent years, responsive nanomaterials have demonstrated tremendous potential in biomedical applications due to their unique advantages in precise drug delivery and controlled release. For complex diseases such as cancer, chronic inflammation, and genetic disorders, traditional treatment methods are often limited by insufficient targeting and significant side effects. Responsive nanotechnology, by sensing specific internal or external stimuli, has significantly enhanced the precision and efficiency of treatments. This study systematically summarizes the technological trajectory and emerging research directions of responsive nanomaterials through global patent and literature data, employing main path analysis, derivative path analysis, and keyword co-occurrence analysis. The results reveal the evolution of this field, from the optimization of early single-stimulus-responsive nano delivery systems to the rise of theranostics integration, followed by advancements in multi-stimuli-responsive synergistic therapies, and finally, the innovation in biomimetic material design. Each developmental phase has increasingly focused on adapting to complex biological environments, achieving superior targeting performance, and enhancing therapeutic efficacy. Keyword co-occurrence analysis highlights key research hotspots, including biomimetic design, multimodal synergistic therapies, and emerging response mechanisms. In the future, responsive nanomaterials are expected to play a pivotal role in personalized medicine, multifunctional carrier design, and complex disease management, providing novel insights and technological support for precision medicine.